Ethnomathematics explorations on the concept of two-dimensional shape in “Tadulako Bulili” folk story - Indah Suciati; Windra Windra; Al-Afandi Al-Afandi; Hajerina Hajerina; Siti Hadija Alaydrus (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
To explore the folklore of Tadulako Bulili as a literacy medium in learning the two-dimensional shape, a qualitative descriptive study was carried out with an ethnographic approach. Methods of observation, interviews, documentation, and literature studies were used to collect research data, which were analyzed using the Miles & Huberman interactive model. The subjects of this study were traditional leaders, 3rd-grade elementary school teachers, lecturers, and several students who lived in Sigi Regency. The findings show that Tadulako Bulili's folklore can be thematic contextual learning in two-dimensional material that supports Ausubel, Bruner, and Gagne's learning theory. The results found four fundamental mathematical activities: counting, locating, designing, and explaining. In addition, various two-dimensional shapes were found in the illustrations of objects in the story. The exploration results also provided knowledge and information on the mention of two-dimensional shapes in the Kaili language and replicas of objects that were thought to be found in the story. Folklore could also introduce students to the local wisdom of Central Sulawesi, such as traditional houses, traditional weapons, hunting and farming tools, and the stories themselves.